1998
DOI: 10.1046/j.1365-2141.1998.00873.x
|View full text |Cite
|
Sign up to set email alerts
|

Minimal residula disease status as a predictor of relapse after allogenic bone marrow transplantation for children with acute lymphoblastic leukaemia

Abstract: Summary.We have analysed the behaviour of minimal residual disease (MRD) after allogeneic bone marrow transplantation (allo-BMT) in 71 children with acute lymphoblastic leukaemia (ALL). The method relied on PCR of IgH, TCRd and/or TCRg gene rearrangements followed by electrophoretic size resolution and allele-specific oligoprobing. Patients were similarly conditioned; 55 received marrow from unrelated donors and 16 from related donors. MRD was assessed at various time-points up to 24 months after BMT. Three ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
122
2
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(137 citation statements)
references
References 47 publications
12
122
2
1
Order By: Relevance
“…To this date, the impact of MRD before transplantation in childhood ALL has only been addressed in studies with a relatively small number of patients. 19,26,27 In this study, including 170 patients with a median follow-up of 4 years, we have shown that MRD before UCBT is a strong predictive Leukemia Free Survival Figure 2. The estimated 4-year probability of LFS in children with ALL in remission by MRD status before UCBT.…”
Section: Discussionmentioning
confidence: 69%
“…To this date, the impact of MRD before transplantation in childhood ALL has only been addressed in studies with a relatively small number of patients. 19,26,27 In this study, including 170 patients with a median follow-up of 4 years, we have shown that MRD before UCBT is a strong predictive Leukemia Free Survival Figure 2. The estimated 4-year probability of LFS in children with ALL in remission by MRD status before UCBT.…”
Section: Discussionmentioning
confidence: 69%
“…Knechtli et al 13 observed post transplant MRD positivity in 8 of 36 patients who remained in continuing complete remission. All MRDpositive samples in their study had been followed by negative ones, compared to 9 of 16 positive samples in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Several groups, including ours, reported the unfavorable prognostic significance of high MRD levels before transplant in children with high-risk ALL. [5][6][7][8] Studies exploring the significance of post transplant MRD were based on the detection of mixed chimerism, 9,10 flow cytometry (FC), 11 the fusion gene PCR in case of Ph þ ALL, 12 PCR using clone-specific Ig or TCR V-(D)-J sequences [13][14][15][16] and, most recently, real-time quantitative PCR (RQ-PCR) detection of clonal Ig/TCR rearrangements. 17 Consistently, all studies showed that detectable MRD at any time after SCT represents a substantial risk of post transplant relapse, both in children and in adults.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Many contemporary treatment protocols are testing the clinical utility of monitoring MRD and others have already incorporated MRD studies to aid the selection of postremission induction therapies. 12,13 MRD assays have also shown utility for patients undergoing hematopoietic stem cell transplantation, [14][15][16][17] and provide a novel parameter to assess the efficacy of emerging novel antileukemic agents. 18 Among the available methods for MRD detection in ALL, flow cytometric analysis of abnormal immunophenotypes and polymerase chain reaction (PCR) amplification of antigen-receptor genes are the most widely used.…”
Section: Introductionmentioning
confidence: 99%